การศึกษาความสัมพันธ์ระหว่างผลิตภาพแรงงานและค่าจ้างระหว่างภาคของประเทศไทย - สันติ ปะมะโข (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
This thesis is a study of a relationship between regional labor productivity and wages in Thailand. Most of the studies about this relationship analyze only in a country level but not regional. In Thailand, there was a development of Multi-Regional Input-Output Table (MRIO) that can provide regional and sectoral information. However, the MRIO does not have the data about the number of workers in each sector and region. Thus, the objectives of this study are 1) to classify the number of workers data and make it consistence with the MRIO data, 2) to analyze the relationship between labor productivity and wages across regions and sectors of production in Thailand, and 3) to analyze the impact on regional and sectoral employment if there is a change in final demand. Results of this study indicate that industrial sector in the eastern region of Thailand has a high level of positive relationship between labor productivity and wage. The data in this region also show that the capital-labor ratio is high, and the amount of skilled labor is also high. According to Jain (2019),  Furthermore, in an analysis of final demand change, the change has a big impact on employment of the livestock sector in the northeastern region of Thailand through backward linkages, and the cassava sector in the northeastern region of Thailand through forward linkages.